Roles of activating functions 1 and 2 of estrogen receptor α in lymphopoiesis. Issue 2 (February 2018) - Andersson, Annica; Törnqvist, Anna E; Moverare-Skrtic, Sofia; Bernardi, Angelina I; Farman, Helen H; Chambon, Pierre; Engdahl, Cecilia; Lagerquist, Marie K; Windahl, Sara H; Carlsten, Hans; Ohlsson, Claes; Islander, Ulrika
Abstract : Apart from the role of sex steroids in reproduction, sex steroids are also important regulators of the immune system. 17β-estradiol (E2) represses T and B cell development, but augments B cell function, possibly explaining the different nature of immune responses in men and women. Both E2 and selective estrogen receptors modulators (SERM) act via estrogen receptors (ER). Activating functions (AF)-1 and 2 of the ER bind to coregulators and thus influence target gene transcription and subsequent cellular response to ER activation. The importance of ERαAF-1 and AF-2 in the immunomodulatory effects of E2/SERM has previously not been reported. Thus, detailed studies of T and B lymphopoiesis were performed in ovariectomized E2-, lasofoxifene- or raloxifene-treated mice lacking either AF-1 or AF-2 domains of ERα, and their wild-type littermate controls. Immune cell phenotypes were analyzed with flow cytometry. All E2 and SERM-mediated inhibitory effects on thymus cellularity and thymic T cell development were clearly dependent on both ERαAFs. Interestingly, divergent roles of ERαAF-1 and ERαAF-2 in E2 and SERM-mediated modulation of bone marrow B lymphopoiesis were found. In contrast to E2, effects of lasofoxifene on early B cells did not require functional ERαAF-2, while ERαAF-1 was indispensable. Raloxifene reduced early B cells partly independent of both ERαAF-1 and ERαAF-2. Results from this study increase the understanding of the impact of ER modulation on the immune system, which can be useful in the clarification of the molecular actions of SERMs and in the development of new SERM.